Bibliometric Analysis of Pakistani Medical Journals Evidenced Exponential Growth of Coronavirus Disease–Related Publications. Issue 1 (2nd January 2023) - Ullah, Midrar
Abstract: Since 2019, the novel coronavirus disease (COVID-19) has transformed into a global pandemic, and studies on COVID-19 are crucial in finding solutions to deal with the pandemic. The objective of this study is to present a bibliometric analysis of COVID-19–related literature published in Pakistani medical journals. In this study, the PakMediNet database was searched for COVID-19–related literature on February 11, 2022. The required bibliometric data of each publication were documented in Microsoft Excel. About 67% of the 480 articles found were original articles, among which the vast majority (99%) were published in 2021 and 2022. Hamzaullah Khan, Pakistan Journal of Medical Sciences, and the National University of Medical Sciences were the most prolific author, journal, and institution, respectively. The most cited publication received 491 citations. Psychology and public health were the most preferred subjects. Pakistani medical journals have published a significant number of publications on COVID-19. However, international contributions and citations of these publications were low.